2020
DOI: 10.3390/genes11040352
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of HMOX1 Gene in Hezuo Tibetan Pigs: Roles of WT1, Sp1, and C/EBPα

Abstract: Heme oxygenase 1 (HMOX1) is a stress-inducing enzyme with multiple cardiovascular protective functions, especially in hypoxia stress. However, transcriptional regulation of swine HMOX1 gene remains unclear. In the present study, we first detected tissue expression profiles of HMOX1 gene in adult Hezuo Tibetan pig and analyzed the gene structure. We found that the expression level of HMOX1 gene was highest in the spleen of the Hezuo Tibetan pig, followed by liver, lung, and kidney. A series of 5’ deletion promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It remains to be determined whether zoledronic acid and EF24 activate the same or different pathway to upregulate HMOX1 in osteosarcoma cells. HMOX1 gene transcription can be subjected to complex regulation involving different transcription factors such as WT1, Sp1, C/EBPα, and Nrf2 ( Wang et al, 2020 ; Zhang et al, 2021 ). Further studies are required to delineate which of these factors mediates zoledronic acid-induced increase in HMOX1 mRNA expression in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether zoledronic acid and EF24 activate the same or different pathway to upregulate HMOX1 in osteosarcoma cells. HMOX1 gene transcription can be subjected to complex regulation involving different transcription factors such as WT1, Sp1, C/EBPα, and Nrf2 ( Wang et al, 2020 ; Zhang et al, 2021 ). Further studies are required to delineate which of these factors mediates zoledronic acid-induced increase in HMOX1 mRNA expression in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…HMOX1 is a stress‐inducible enzyme 32 . The HMOX1 promoter regulates transcription through polymorphisms in response to oxidative stress 33 .…”
Section: Discussionmentioning
confidence: 99%
“…HMOX1 is a stress-inducible enzyme. 32 The HMOX1 promoter regulates transcription through polymorphisms in response to oxidative stress. 33 In addition, BACH1 has an endogenous heme ligand that investigated the levels of plasma metabolites in patients with lumbar disc herniation and found that glutamate, aspartate, and glycine levels were elevated, and the content of glucose 1-phosphate was diminished.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the factors regulating RIP2 expression activity, we firstly analyzed and identified the core promoter region of chicken RIP2 . Luciferase reporter gene vector utilized in this study is a common method for many studies of the promoter activity and core regulatory regions [ 43 , 44 , 45 ]. Meanwhile, chicken HD11 and DF1 cells were used as experimental models to double check the promoter activity of RIP2 .…”
Section: Discussionmentioning
confidence: 99%